2022
DOI: 10.1007/s11886-022-01754-w
|View full text |Cite
|
Sign up to set email alerts
|

Focus on Diagnosis and Prognosis to Guide Timing of Intervention in Valvular Heart Disease

Abstract: Purpose of Review The present article reviews the role of multimodality imaging to improve risk stratification and timing of intervention in patients with valvular heart disease (VHD), and summarizes the latest developments in transcatheter valve interventions. Recent Findings Growing evidence suggests that intervention at an earlier stage may improve outcomes of patients with significant VHD. Multimodality imaging, including strain imaging and tissue char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…[10][11][12][13] While the data supporting the reliability of quantitative TR grading as an independent predictor of clinical outcomes, in a recent meta-analysis of 70 studies, just one study reported findings utilizing such grading, which is superior to qualitative assessment. 3,5 The emphasis shifted to the usefulness of the PISA method for TR grade due to the potential underestimating of the TR severity with biplanar measurement of VC. the persistent rise in mortality linked to EROA >20 mm 2 and regurgitant volume (RegV) >20 mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] While the data supporting the reliability of quantitative TR grading as an independent predictor of clinical outcomes, in a recent meta-analysis of 70 studies, just one study reported findings utilizing such grading, which is superior to qualitative assessment. 3,5 The emphasis shifted to the usefulness of the PISA method for TR grade due to the potential underestimating of the TR severity with biplanar measurement of VC. the persistent rise in mortality linked to EROA >20 mm 2 and regurgitant volume (RegV) >20 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Around 4% of persons 75 and older have moderate or severe TR 1,2 . Recent data from numerous studies suggest that significant TR adversely affects patient prognosis and does so more and more with each increase in severity grade 3–5 . This could make sense given that chronic right ventricle (RV) volume overload brought on by severe self‐perpetuating TR may cause the RV to enlarge and remodel over time, which could then result in gradual, irreversible RV myocardial injury and right heart failure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Mortality due to AVD has steadily increased from the 1970s to the 2000s, with an annual increase of approximately 1.6% [ 11 ]. In addition, AS prevalence is increasing in ageing populations and carries significant risks [ 12 ]. If left untreated, symptomatic severe AS can have a mortality of 75% at 3.5 years, with up to 50% of those affected dying suddenly [ 13 ].…”
Section: Introductionmentioning
confidence: 99%